Analysis the Role of Accounting Information System in Increasing Sales of MSME at Benteng Pancasila Market, Mojokerto City - Dwi Cahyadi, Semmuel; Mutia Edwy, Ferby (Dinasti Publisher, 2025)
This study aims to analyze the role of Accounting Information System in improving the Performance of Sales Incentives in MSME traders at the Pancasila Fort Market, Mojokerto City on the implementation of the Accounting Information System in improving sales accounting performance. MSMEs have an important role in the Indonesian economy, but still face obstacles in accurate and efficient financial records. The use of Accounting Information System, such as Zahir Accounting, Accurate Online, and Jurnal by Mekari, is expected to help traders manage transactions and financial reports more systematically. This study uses a descriptive qualitative method with data collection techniques through structured interviews and direct observation of 19 MSME traders who have implemented Accounting Information System. The results of the study show that Accounting Information System provides significant benefits in supporting transaction recording, stock management, and automatic financial reporting. In addition, this system also helps traders in controlling cash flow and making business decision-making easier. However, there were some obstacles, such as initial difficulties in understanding the features, relatively high subscription fees, and dependence on internet connections. The results of this study are in line with Suhartini's (2020) theory which identifies eight main benefits of Accounting Information System for businesses. As a solution, it is necessary to improve digital literacy and accounting for MSME traders through training or technical assistance. In addition, Accounting Information System service providers can provide more flexible packages for small MSMEs. Thus, the wider implementation of Accounting Information System is expected to improve business efficiency and the sustainability of MSMEs in Mojokerto City.